2023
DOI: 10.1007/s00535-023-02009-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID-19 pandemic on the diagnosis, stage, and treatment of esophagogastric cancer

Abstract: Background The COVID-19 pandemic has affected the entire global healthcare system, including oncological care. This study investigated the effects of the COVID-19 pandemic on the diagnosis, stage, and treatment of esophagogastric cancer in the Netherlands. Methods Patients diagnosed in 2020 were divided into 5 periods, based on the severity of the COVID-19 pandemic in the Netherlands, and compared to patients diagnosed in the same period in the years 2017–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
(29 reference statements)
0
0
0
Order By: Relevance
“…The COVID-19 pandemic, especially the first waves, had a huge impact on cancer care: cancellation of consultations, screening and diagnostic tests and surgeries; medical material scarcity; fear to go to the hospital; and patients who contracted COVID-19, among others[ 35 , 36 ]. In our series, seven patients lost their opportunity to undergo surgery with a curative intent during the first wave.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic, especially the first waves, had a huge impact on cancer care: cancellation of consultations, screening and diagnostic tests and surgeries; medical material scarcity; fear to go to the hospital; and patients who contracted COVID-19, among others[ 35 , 36 ]. In our series, seven patients lost their opportunity to undergo surgery with a curative intent during the first wave.…”
Section: Discussionmentioning
confidence: 99%
“…A Dutch study reported a decrease in esophageal cancer patients in 2020 and an increase in the proportion of patients with incurable esophageal and stomach cancer. They suggest that this was owing to patients with mild symptoms refraining from medical visits [26]. An English study reported a 37% decrease in hepatocellular carcinoma patients in 2020.…”
Section: Introductionmentioning
confidence: 99%